2019
DOI: 10.29303/jmm.v8i3.448
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Artificial Intelligence dan Digital Marketing terhadap Minat Beli Konsumen

Abstract: The purpose of this paper is to investigating the influence of Artificial Intelligence and Digital Marketing to Consumers Buying Intention. Artificial Intelligence development revolutionize digital marketing as well as customer buying intention and thus boost sales. Artificial Intelligence and Digital Marketing in combination with rapidly developing technologies kind of tracking, buying, cashless. Everything goes to simple touch, will bring opportunities to consumers to having a practical best service. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 1 publication
0
4
0
5
Order By: Relevance
“…From the research hypothesis mentioned above, this conceptual framework is modified from Pangkey et al [3] and Maurer and Liu [10], due to limited quantitative research with subject AI on recruitment process in Indonesia and overseas country, authors combining the conceptual framework from previous studies and the result can be seen in Figure 1 below. Figure 1, described research model of this study, the independent variable is Artificial Intelligence (AI) and Virtual Recruitment Environment (VRE), mediating variable in this model is e-HRM, and dependent variable is recruitment process (REK).…”
Section: Research Hypothesis and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…From the research hypothesis mentioned above, this conceptual framework is modified from Pangkey et al [3] and Maurer and Liu [10], due to limited quantitative research with subject AI on recruitment process in Indonesia and overseas country, authors combining the conceptual framework from previous studies and the result can be seen in Figure 1 below. Figure 1, described research model of this study, the independent variable is Artificial Intelligence (AI) and Virtual Recruitment Environment (VRE), mediating variable in this model is e-HRM, and dependent variable is recruitment process (REK).…”
Section: Research Hypothesis and Conceptual Frameworkmentioning
confidence: 99%
“…The result from previous research related to the turnover rate in Indonesia, with target of the millennial workers showed that only 25% of millennial workers are feeling involve with the companies, while 9% of millennial workers are felt not tied to the company, and 66% are partially feel bounding with the company. 60% of millennial workers are considering leaving the organization if they don't feel fit with the company [3]. This phenomenon will certainly affects the turnover rates of a company and might impact organization performance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sehingga setiap perusahaan harus dapat menyesuaikan strategi pemasaran dengan berpindah ke media online atau biasa disebut digital marketing. Pangkey et al (2019) tersebut memenuhi jumlah sampel yang dibutuhkan untuk penelitian yaitu antara 30-500 (Ghozali, 2011;Sekaran, 2003). Teknik yang digunakan untuk pengambilan sampel pada penelitian ini yaitu non-probability sampling berupa purposive sampling yaitu pengambilan sampel menggunakan karakteristik tertentu yang berhubungan dengan karakteristik populasi, yaitu konsumen yang pernah berbelanja di marketplace Tokopedia, pernah mengakses website Tokopedia, melakukan pencarian Tokopedia di mesin pencari, menerima e-mail dari Tokopedia, dan mengakses media sosial Tokopedia.…”
Section: Hubungan Antara Digital Marketing Dengan Minat Beliunclassified
“…Artificial intelegence (AI) pada era Society 5.0 mengolah big data untuk memfasilitasi berbagai kebutuhan manusia. Implementasinya kini telah ada di berbagai sektor (Nilsson, 2014;Pangkey, Furkan, & Herman, 2019;Tjandrawinata, 2016). Sebut saja pelayanan rumah pintar seperti adanya CCTV, robot pembersih rumah dan mesin pintar sebagai pelayan.…”
Section: Pendahuluanunclassified